Hypoxic MSCs Reduce UV-B Collagen Loss by Modulating CD68 and TNF-α Expression - Ati, Sri Umi; Putra, Agung; Sumarawati, Titiek; Setiawan, Eko; Ibrahim, Sugeng; Taskworo, Dodik (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Ultraviolet-B (UV-B) radiation-induced skin photoaging is marked by collagen degradation and chronic inflammation, with limited effective treatments currently available. Hypoxic-preconditioned mesenchymal stem cells (H-MSCs) offer a novel therapeutic approach due to their immunomodulatory capabilities. This study evaluated the effects of H-MSCs at two doses (2.5×105 and 5×105 cells) on UVB-induced collagen loss, focusing on CD68 expression and TNF-α levels in a rat model. Male Wistar rats were divided into five groups: healthy controls, UV-B-exposed negative controls (saline), positive controls (hyaluronic acid), and two H-MSC-treated groups. After UV-B exposure (160 mJ/cm², five times per week for two weeks), validated H-MSCs were administered subcutaneously. Collagen content was assessed histologically, while CD68 gene expression and TNF-α levels were measured by qRT-PCR and ELISA, respectively. UVB exposure led to significant reductions in collagen and increased levels of inflammatory markers. H-MSC treatment showed dose-dependent anti-inflammatory effects, with the higher dose (5×105 cells) optimally reducing CD68 expression and TNF-α levels, nearly matching healthy controls. These results suggest that H-MSCs, particularly at higher doses, may be a promising therapy for UVB-induced skin damage and collagen loss.